Effects of meso training cycles on cardiovascular and respiratory efficiency in soccer players from the UNAH-TEC Danlí Regional Centre - Figueroa-Soriano, R. O.; Martínez-Saravia, N. D.; Gaitan-Amador, R. A. (Journal of Human Sport & Exercise, 2021)
The study consisted of the analysis of the effects of sports training planning through the combination of meso cycles that contribute to the improvement of physical preparation: Cardiovascular and Respiratory Efficacy of UNAH-TEC-Danlí footballers in the 2019 season of the Major League Pedro Nufio Category A. The effectiveness of the meso cycles with the specific load components for the treatment of physical preparation in the players was validated, belonging to a sample of 30 subjects, where in the pre-test moments and post-test, the QUERG tests were applied to assess the Cardiovascular Efficiency, Cooper for the maximum oxygen consumption where the correlation between the variables of Cardiac Efficiency and Respiration of the experiment was determined to generate probabilities and significance between them. Pearson's correlation, showing a moderate negative correlation index between the study variables, in this sense the conclusions and acceptance of the proposal were established and the objective of the research was met.